2023
DOI: 10.1101/2023.07.24.550282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and single-nucleus transcriptomic analysis of genetic and sporadic forms of Alzheimer’s Disease

Abstract: The pathogenesis of Alzheimer's disease (AD) depends on environmental and heritable factors, with remarkable differences evident between individuals at the molecular level. Here we present a transcriptomic survey of AD using spatial transcrip- tomics (ST) and single-nucleus RNA-seq in cortical samples from early-stage AD, late-stage AD, and AD in Down Syndrome (AD in DS) donors. Studying AD in DS provides an opportunity to enhance our understanding of the AD transcriptome, potentially bridging the gap between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…We integrated our dataset from TC region (GM and WM) to other published studies from different brain regions that include entorhinal cortex 10,11 (Leng et al 8 , Grubman et al 9 ), prefrontal cortex 12,13,5 (Cain et al 12 , Zhou et al 13 , Mathys et al 5 ), superior frontal gyrus 10 (Leng et al 10 ) and deep white matter from prefrontal cortex 12 (Cain et al 12 ). The matrix of filtered UMI counts (>500) for each study was converted to a single cell experiment (SCE) object using the function read10xCounts from SingleCellExperiment 45 package on R (version 4.0.1) platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We integrated our dataset from TC region (GM and WM) to other published studies from different brain regions that include entorhinal cortex 10,11 (Leng et al 8 , Grubman et al 9 ), prefrontal cortex 12,13,5 (Cain et al 12 , Zhou et al 13 , Mathys et al 5 ), superior frontal gyrus 10 (Leng et al 10 ) and deep white matter from prefrontal cortex 12 (Cain et al 12 ). The matrix of filtered UMI counts (>500) for each study was converted to a single cell experiment (SCE) object using the function read10xCounts from SingleCellExperiment 45 package on R (version 4.0.1) platform.…”
Section: Methodsmentioning
confidence: 99%
“…Although the complex pathophysiology of AD remains poorly understood, recent transcriptomic and epigenomic analyses have revealed that post-mortem human AD brain tissue exhibits downregulation of genes associated with neuronal function 4,5 and upregulation of the genes involved in the innate immune response 6,7 . However, not many studies have looked systematically at the spatial distribution of gene expression and its relationship to neuropathology 8 . Thus, our overall understanding of cell type heterogeneity and compositional changes during pathological accumulation is still under-explored, hindering our ability to understand the biological processes underlying AD 9 .…”
Section: Mainmentioning
confidence: 99%
“…(2021), Miyoshi et al. (2023), and Seattle Alzheimer's Disease Brain Cell Atlas (SEA‐AD), 23 , 42 , 55 , 56 , 57 , 58 totaling 349 samples, 1.3 million cells, and 25k genes after the initial QC process (Figure 1B ). While analysis approaches are continually evolving, we have adopted the following workflow for single cell/nucleus RNA‐seq studies, inspired by the guidelines by Luecken et al.…”
Section: Single‐nucleus Transcriptomics Elucidates Cell Type–specific...mentioning
confidence: 98%
“…For demonstrating the pipeline, we have merged snRNA-seq data from the following publications in the field of AD and dementia asso- Alzheimer's Disease Brain Cell Atlas (SEA-AD), 23,42,[55][56][57][58] totaling 349 samples, 1.3 million cells, and 25k genes after the initial QC process (Figure 1B). While analysis approaches are continually evolving, we have adopted the following workflow for single cell/nucleus RNA-seq F I G U R E 1 Schematic workflow of single-cell/nucleus data acquisition and analysis.…”
Section: Demonstration and Walk-through Of Snrna-seq Analysis Approachesmentioning
confidence: 99%
“…DS is both a neurodevelopmental and neurodegenerative disorder and and artificial intelligence with machine learning, will allow unique indepth analysis of these valuable brain tissues as reported by members of the DSBC (e.g., 55 ).…”
Section: Limitationsmentioning
confidence: 99%